Scaling up of starve fed single screw extrusion - Nastaj, Andrzej (Polimery, 2021)
A method of scaling up the starve fed single screw extrusion of polymers has been developed. The research was carried out on the basis of a computer model of the process with the use of genetic algorithms (evolutionary techniques). The basis of the method is the GSEM (Global Screw Extrusion Model) extrusion simulation program, which is the source of data for optimization, and the specially developed GASES ST (Genetic Algorithm Screw Extrusion Scaling for Starve) program. The work involved changing the scale from the extruder with the screw diameter D = 45 mm to the extruder with D = 60 mm, while maintaining the same L/D ratio. Based on the simulation, the rotational screw speed, the temperature of individual zones of the plasticizing unit and the feeding rate were optimized. Scaling up was carried out according to the criteria of energy unit consumption, polymer melting rate and die temperature.